Effectiveness of sangre de drago (croton lechleri sp) in the healing of post exodontics in adults - Cavalie Martel, Karina P. (2019)
Dental caries is among the ten leading causes of morbidity in the country and in our region, ending mostly in exodontia, resulting in a postexodontic wound with risks of bleeding, infections and other oral health problems. The objective research was to determine the effectiveness of croton lechleri sp in postexodontic wound healing. The methodology research carried out was a quasi-experimental study with 50 adults from a Private Dental Clinic in Huánuco, 2015. An observation guide research was used in the collection of information on post orthodontic wounds. In the inferential analysis of the results used the U Mann-Whitney Test. Results: the average healing time of the postexodontic wound in the experimental group was 18.3 days and the control group was 27.1 days. Likewise, in the experimental group, the average time of disappearance of pain, edema, erythema, bleeding and clot formation was 1,5; 2,2; 2,2; 1,1 and 2,1 days and of the control group of 3.5; 3.8; 3.8; 2.2 and 3.8 days, respectively. All presented statistically significant differences (P≤0,000). Conclusions: The effectiveness of croton lechleri sp allowed the reduction of the average healing time of the postexodontic wound and also the early disappearance of the signs and symptoms of the wound.